Latent Multi-drug Resistant Tuberculosis: An Unaddressed Problem - Gyanshankar Mishra; Jasmin Mulani (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
It is estimated that three of every 1,000 individuals worldwide have latent Multidrug-Resistant Tuberculosis (MDR-TB) infection. Management of latent MDR-TB is an integral component in our strategies targeting global TB elimination. We are currently targeting only latent drug-sensitive TB as there are no consensus guidelines on the management of latent MDR-TB. Such an approach can potentially lead to a "fall and rise phenomenon" in latent MDR-TB. Risk factors for latent MDR-TB need to be identified, and high-risk individuals need to be screened and treated on priority for latent MDR-TB. The treatment of latent MDR-TB can be initiated primarily with fluoroquinolones-based treatment regimes. Such regimes need to be individualized based on the drug sensitivity pattern of the source case isolate of drug-resistant TB. Thus, strategies for managing latent MDR-TB are the need of the day.